GROING NEIGHBORHOOD GARDENING TEAMS IN THE TIME OF COVID - Patricia, Mckenna Verschelden (My University, 2020)
Abstract The COVID-19 pandemic is a crushing example of humanity’s vulnerability to the natural world of which we are a part. Humanity’s continued expansion into the last wild places, combined with destabilizing climate patterns that shift habitats of disease vectors, make novel disease outbreaks an expected occurrence. The development of a novel coronavirus strain is only one of many environmental changes that will challenge us now and in the future. My dual internships with the Riley County Health Department’s Contact Tracing team and UFM Community Learning Centers GRO Initiative, each sought to mount an effective response to these changes. Contact tracing seeks to reduce transmission of COVID-19 by reaching community members who test positive for the virus and those that they have come in contact with and provide timely and accurate recommendations for quarantine and isolation. By keeping these community members isolated from others during their infectious period, transmission is reduced. The GRO Initiative is designed to increase access to healthy foods through organizing community members to grow food together and share it. The intention is for community members of all incomes, backgrounds, and experience levels to be able to participate, learn and share their skills around gardening with one another. Over time, local food production capacity and mutual support will grow, helping Manhattan, Kansas be a resilient community in an uncertain future.
Keywords: community gardens; social capital; food security; climate change; resiliency; contract tracing